2022
DOI: 10.3390/biomedicines10040919
|View full text |Cite
|
Sign up to set email alerts
|

miR-195-5p Regulates Tight Junctions Expression via Claudin-2 Downregulation in Ulcerative Colitis

Abstract: Inflammatory bowel disease (IBD) is characterized by chronic intestinal inflammation associated with an increased intestinal permeability. Several studies have shown that microRNAs (miRNAs) are involved in the IBD pathogenesis. Here, we aimed to functionally characterize the role of miRNAs in the regulation of intestinal permeability and barrier function. We identified 18 dysregulated miRNAs in intestinal epithelial cells (IECs) from the ulcerative colitis (UC) mice model and control mice. Among them, down-reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…Recently, roles for miR-195-5p have been reported in many diseases such as preeclampsia ( Zhou et al, 2022 ), inflammatory bowel disease ( Scalavino et al, 2022b ), cerebral ischemia-reperfusion (I/R) injury ( Ren et al, 2021 ) and colorectal cancer ( Lin et al, 2019 ). miR-195-5p is a critical regulator of many biological events such as cell proliferation and invasion ( Wang et al, 2021 ), oxidative stress ( Xia et al, 2022 ) and redistribution of tight junctions ( Scalavino et al, 2022a ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, roles for miR-195-5p have been reported in many diseases such as preeclampsia ( Zhou et al, 2022 ), inflammatory bowel disease ( Scalavino et al, 2022b ), cerebral ischemia-reperfusion (I/R) injury ( Ren et al, 2021 ) and colorectal cancer ( Lin et al, 2019 ). miR-195-5p is a critical regulator of many biological events such as cell proliferation and invasion ( Wang et al, 2021 ), oxidative stress ( Xia et al, 2022 ) and redistribution of tight junctions ( Scalavino et al, 2022a ).…”
Section: Introductionmentioning
confidence: 99%
“…In our recent paper, starting from a miRNA expression profiling of intestinal epithelial cells of an ulcerative colitis mice model, we demonstrated that miR-195-5p resulted downregulated in ulcerative colitis. Moreover, we proved that the intracellular increase of miR-195-5p in colonic epithelial cells led to a decrease of CLDN2 and indirectly, also CLDN1 [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our recent work, we demonstrated that miR-195-5p was able to maintain barrier integrity, regulating the TJs expression [ 29 ]. In the present study, we aimed to investigate whether miR-195-5p modulates the expression of CLDN2 and the other TJs protein expression also under inflammatory conditions induced by TNF-α stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…This increased expression can be attributed to the effect of the inflammatory cytokine IL-6, which is found in abundance in IBD patients [ 124 ]. Conversely, the microRNA miR-195-5p, which is reduced in UC patients in comparison to healthy controls, can impede the expression of these two claudins [ 125 ]. Furthermore, miR-24 is another microRNA that has been revealed to be specifically elevated in the colon tissue and even the blood of UC patients.…”
Section: Leaky Gut and Diseasesmentioning
confidence: 99%